Quality of life of veterans of sports with osteochondrosis of the lumbosacral spine - Oleksiy Goncharov (Слобожанський науково-спортивний вісник, 2018)
Purpose: to establish the effect of a comprehensive program of physical rehabilitation on the quality of life of wrestlers – veterans of sports with osteochondrosis of the lumbosacral spine in the training motor regime. Material & Methods: 34 athletes-veterans at the age of 36–45 years, a kind of struggle – judo and sambo-wrestling took part in the study. Sports qualification of athletes: MS – 25 people, MSIG – 9 people. The test was carried out on the verbal assessment scale of pain, the degree of vertebro-neurological disorders was assessed, the standard of living for the Oswestrovsky questionnaire was determined. Results: after application of the proposed comprehensive physical rehabilitation program for wrestlers – veterans of sports of the MG in 68% of cases, complaints were absent, the degree of vertebro-neurological disorders decreased, the results of the questionnaire on the Oswestrovsky questionnaire showed a statistically significant decrease in complaints of pain in various spheres of life. Conclusion: the positive influence of the developed program of physical rehabilitation on the quality of life of wrestlers – veterans of sports are proved.